Pengembangan Media Pembelajaran Pola Lantai Menggunakan Aplikasi Pyware 3D Interactive Pada Guru Seni Budaya Tingkat SMP - Khusnul, Fitria (Program Studi Pendidikan Tari FBS UNJ, 2024)
This thesis discusses problems using conventional learning media in floor pattern material is the main thing during learning. The purpose of this study to explain the process and analyze the results of the feasibility test for the development of dance learning media based on the Pyware 3D Interactive application on floor pattern material. The research method used is research and development or R&D (Research and Development) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. This is done by limiting it to the small-scale trial stage. Based on the results of small-scale trials from the assessment of learning experts and media experts with the result